Development of portable traditional triple mouth chula (Journal of the Bangladesh Agricultural University, 2010)
In rural areas of Bangladesh almost in every house earthen Chula is used for cooking purpose. Mostly single mouth Chula is used in this purpose. The Heat Use Efficiency (HUE) of this Chula is needed to be increased by proper design for better utilization of fire wood to reduce the cost of cooking especially in the rural areas of Bangladesh. In this regard the effect of dimensions such as hearth height and diameter of the traditional single-mouth Chula on HUE were tested. The effects of dimensions of triple mouth Chula on HUE were also tested. Thus varieties of single mouth and triple mouth Chula both series and triangular were constructed. The variations of triple mouth Chula were made on size and shape, fuel inlet and exit, providing stone and without stone, providing lid and without lid etc. The HUE of single mouth Chula was found varied from 17.02% to 22.3%.The maximum HUE of triple mouth Chula was found varied from 31.52% to 39.74%. The highest HUE of this Chula was found to be 39.74% in earthen Chula encased with iron drum. This most efficient Chula has identity of separate air entry with stone, fuel inlet and smoke and ash exit at bottom. It is portable and its cost is with in the afford of rural people. It can be made even cheaper by making with only soil. Thus it can be produced commercially which can save fire wood, money as well as time of the user. Keywords: Heat use efficiency; Portable; Triple mouth Chula DOI: 10.3329/jbau.v8i1.6411J. Bangladesh Agril. Univ. 8(1): 141-145, 2010